The electromagnetic gauge invariance in SU(3)L ⊗ U(1)N models of electroweak unification reexamined - Pleitez, Vicente [UNESP]; Tonasse, M. D. (Elsevier B.V., 1998)
Two models with SU(3)C ⊗ SU(3)L U(1)N gauge symmetry are considered. We show that the masslessness of the photon does not prevent the neutrinos from acquiring Majorana masses. That is, there is no relation between the VEVs of Higgs fields and the electromagnetic gauge invariance contrary to what has been claimed recently. © 1998 Elsevier Science B.V. All rights reserved.